Design high voltage gain DC converter based on maximum power point resistance for photovoltaic applications - Ibraheem Jawad Billy; Jasim Farhood Hussein (Bulletin of Electrical Engineering and Informatics, 2023)
Due to the nonlinear properties of photovoltaic (PV) modules, the design of the high-gain direct current (DC) converter for maximum power point tracking (MPPT) is complicated. In this paper, the design of a new step-up DC converter for MPPT applications is proposed. The proposed converter is structured of two symmetrical reverse-parallel DC-DC boost converters. This structure is supported by voltage multiplier cells equipped to increase output voltage and decrease voltage stress on semiconductor switches. To simplify the high-gain DC converter design, the PV module's maximum power point is treated as resistance by using the incremental conductance (INC) method. The MPPT boost converter's inductance, input capacitance, and output capacitance are calculated using the derived equations using nine parameters. The results showed that the proposed DC converter simulation meets the necessary requirements. The size of the input capacitor, inductor, and output capacitor have been decreased. When the proposed converter is compared to a traditional converter, there is less voltage stress, low current ripple, and an increase in voltage gain. This has led to an improvement in the overall converter efficiency.